Myc 9aaTAD activation domain binds to mediator of transcription with superior high affinity - Andrea Knight; Josef Houser; Tomas Otasevic; Vilem Juran; Vaclav Vybihal; Martin Smrcka; Martin Piskacek (BMC, 2024)
Abstract The overexpression of MYC genes is frequently found in many human cancers, including adult and pediatric malignant brain tumors. Targeting MYC genes continues to be challenging due to their undruggable nature. Using our prediction algorithm, the nine-amino-acid activation domain (9aaTAD) has been identified in all four Yamanaka factors, including c-Myc. The predicted activation function was experimentally demonstrated for all these short peptides in transactivation assay. We generated a set of c-Myc constructs (1-108, 69-108 and 98-108) in the N-terminal regions and tested their ability to initiate transcription in one hybrid assay. The presence and absence of 9aaTAD (region 100-108) in the constructs strongly correlated with their activation functions (5-, 3- and 67-times respectively). Surprisingly, we observed co-activation function of the myc region 69-103, called here acetyl-TAD, previously described by Faiola et al. (Mol Cell Biol 25:10220-10234, 2005) and characterized in this study as a new domain collaborating with the 9aaTAD. We discovered strong interactions on a nanomolar scale between the Myc-9aaTAD activation domains and the KIX domain of CBP coactivator. We showed conservation of the 9aaTADs in the MYC family. In summary for the c-Myc oncogene, the acetyl-TAD and the 9aaTAD domains jointly mediated activation function. The c-Myc protein is largely intrinsically disordered and therefore difficult to target with small-molecule inhibitors. For the c-Myc driven tumors, the strong c-Myc interaction with the KIX domain represents a promising druggable target.